Versatile Magnetic Mesoporous Carbon Derived Nano‐Adsorbent for Synchronized Toxic Metal Removal and Bacterial Disinfection from Water Matrices. Issue 15 (8th January 2023) - Saleem, Atif; Chen, Jingjie; Liu, Meng; Liu, Nian; Usman, Muhammad; Wang, Ke; Haris, Muhammad; Zhang, Yuezhou; Li, Peng
Abstract: Contamination of water resources by toxic metals and opportunistic pathogens remains a serious challenge. The development of nano‐adsorbents with desired features to tackle this problem is a continuously evolving field. Here, magnetic mesoporous carbon nanospheres grafted by antimicrobial polyhexamethylene biguanidine (PHMB) are reported. Detailed mechanistic investigations reveal that the electrostatic stabilizer modified magnetic nanocore interfaced mesoporous shell can be programmatically regulated to tune the size and related morphological properties. The core–shell nano‐adsorbent shows tailorable shell thickness (≈20–55 nm), high surface area (363.47 m 2 g −1 ), pore volume (0.426 cm 3 g −1 ), radially gradient pores (11.26 nm), and abundant biguanidine functionality. Importantly, the nano‐adsorbent has high adsorption capacity for toxic thallium (Tl(I) ions (≈559 mg g −1 ), excellent disinfection against Staphylococcus aureus and Escherichia coli (>99.99% at 2 and 2.5 µg mL −1 ), ultrafast disinfection kinetics rate (>99.99% within ≈4 min), and remarkable regeneration capability when exposed to polluted water matrices. The Tl(I) removal is attributed to surface complexation and physical adsorption owing to open ended mesopores, while disinfection relies on contact of terminal biguanidines with phospholipid head groups of membrane. The significance of this work lies in bringing up effective synchronic water purification technology to combat pathogenic microorganisms and toxic metal. Abstract : A unique radially gradient mesoporous nano‐adsorbent has been designed here through a micelle interface assembly approach with tempting antimicrobial moieties. Its application for water purification reveals its dual functionality for highly efficient adsorption of toxic thallium Tl(I) and strong disinfection capability toward Staphylococcus aureus and Escherichia coli bacterial strains.